Development of a rotary clap mechanism for positive-displacement rotary pumps: Pump performance analysis - Shim, Sung-Bo; Park, Young-Jun; Nam, Ju-Seok; Kim, Su-Chul; Kim, Jong-Mun; Kim, Kyeong-Uk (International journal of precision engineering and manufacturing, 2017)
We have introduced a novel positive-displacement rotary pump named as rotary clap pump, and analyzed its working principles through a kinematic analysis in the previous study. That study mainly described fundamental design parameters of the rotary clap pump and their inter-relationships. As a follow-up research, this study presents the pump performance of the rotary clap pump such as the pressure, driving torque, and efficiency characteristics using related theories and some basic assumptions. In the pressure analysis, the effect of friction, mass acceleration, piping components, and gravity were considered. The forces acting on the pump components and the driving torque are calculated using vector equations based on the results of the previous study. The volumetric, torque, and overall efficiencies are analyzed by calculating the slip flow and frictional forces caused by fluid viscosity. We also present the conditions that minimize the input power and forces acting on the components. The experimental study for the rotary clap pump including comparison with analysis results is prepared to the follow-up paper.